The remaining texts of (Turaf Al-dhurafaa) by Al-Shaqandi - Hadaga, Najat Mohamed; Jarrar, Salah Mohammad (Journal of Humanities & Social Sciences, 2021)
The book entitled " Toraf al-Dhorafaa" of Abu al-Walid Al-Shaqondi, is one of the important books of Andalusian literature which have been lost, and it might be discovered one day in one unknown private collection. The distinguished Andalusian Author Abu al-Hasan Ibn sa’aid , is credited with preserving the remaining texts of the book in his books: Al-Moghrib fi hula al-maghrib, Rayat al-Mobarrizin and AlQidh al-mo’alla, since the Father of ibn sa’id was a close friend of Al-Shaqondi. Some late authors like al-Maqqari in his "Nafh al-tib" referred to the books of ibn said when they quoted "Taraf al-Dhorafa." The importance of Al-shaqondi’s book and the great renown of its author incited us to collect all the remaining texts of this book and try as much as we can rebuild it. The number of the biographies we could find reached thirty two biographies, some of them were contemporary to Al- shaqondi, and some are from past periods of the Andalusian history.